CHOROIDAL NEOVASCULARIZATION SECONDARY TO PHOTODYNAMIC THERAPY FOR CENTRAL SEROUS CHORIORETINOPATHY: Incidence, Risk Factors, and Clinical Outcomes. Issue 8 (August 2021) - Hwang, Sungsoon; Noh, Hoon; Kang, Se Woong; Kang, Min Chae; Lee, Dongyoung; Kim, Sang Jin
Abstract : Purpose: To investigate the incidence, risk factors, and clinical outcomes of complicated choroidal neovascularization (CNV) after reduced-fluence photodynamic therapy (PDT) for central serous chorioretinopathy. Methods: This is a retrospective consecutive interventional study including 559 eyes from 520 patients treated by reduced-fluence PDT for central serous chorioretinopathy. The incidence of complicated CNV within 3 months after PDT was calculated. Baseline demographics and ocular findings were investigated to identify risk factors. The clinical course of complicated CNV was analyzed. Results: Seven cases experienced development of active CNV after PDT within 3 months with a median interval of 4 weeks (range, 2–12 weeks). The incidence was estimated as 1.25% (95% CI, 0.55–2.62%). Complicated CNV developed in 6 among 138 eyes (4.35%) with flat irregular pigment epithelial detachment and in 1 among 421 eyes (0.24%) without flat irregular pigment epithelial detachment ( P < 0.001, Fisher's exact test). The median best-corrected visual acuity recovered from 20/100 at the time of CNV development to 20/20 after anti–vascular endothelial growth factor injections (median, 3 times). Conclusion: In approximately 1%, reduced-fluence PDT for central serous chorioretinopathy may be complicated by CNV, which can be well controlled with anti–vascular endothelial growth factor injection. Flat irregular pigment epithelial detachment increases the risk of secondary CNV following PDT. Abstract : Secondary choroidal neovascularization can occur after safety-enhanced photodynamic therapy for central serous chorioretinopathy in approximately 1% of patients. Flat irregular pigment epithelial detachment increases the risk of choroidal neovascularization complicating photodynamic therapy.